PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS IV SD NEGERI 52 LUBUKLINGGAU - Rahman Aditiya; Yadri Irwansyah; Akmal Rijal (LP3MKIL, 2026)
This study aims to determine the completeness of the science learning outcomes of fourth-grade students of SD Negeri 52 Lubuklinggau after the application of Wordwall learning media. This study uses Pre-test and Post-test. Sampling was obtained from the population, the sampling technique in this study is using saturated sampling. The instrument used is in the form of Multiple Choice with a total of 20 questions. The data analysis technique uses the z-test at a significance level of a = 0.05. The results of the study obtained that Zhitung = 5.28> Ztabel = 1.64 so that it is proven that Ha is accepted and Ho is rejected the science learning outcomes of fourth-grade students of SD Negeri 52 Lubuklinggau after the application of Wordwall learning media is significantly complete. The average value is 80.46 and the percentage of students who completed is 88%.